Ethanol biosynthesis by fast hydrolysis of cassava bagasse using fungal amylases produced in optimized conditions - Escaramboni, Bruna [UNESP]; Fernandez Nunez, Eutimio Gustavo [UNESP]; Azevedo Carvalho, Ana Flavia [UNESP]; Oliva Neto, Pedro de [UNESP] (Elsevier B.V., 2018)
The search for a renewable platform to produce high-value biochemicals and energy that are environmentally correct has been a current concern. A fast and inexpensive bioprocess for amylase production, able to hydrolyze complex residues in fermentable sugars to be used for ethanol production was developed. High titer amylase from Rhizopus oligosporus in solid state fermentation (SSF) was obtained by optimizing the medium supplementation using agro-industrial waste as substrate. Statistical experimental design and partial least square (PLS) regression were used to establish a relation between added chemical compounds and enzyme production, showing that urea was the most important nutrient. Crude amylase extract had competitive performance features giving higher productivities in starch hydrolysis than a commercial glucoamylase. The amylase produced was applied in the proportion of 15 U/g dry cassava bagasse to obtain cassava bagasse hydrolysate (CBH). More than 42% conversion in reducing sugars was achieved with an efficient 10 h single-step hydrolysis at 55 degrees C in a bioreactor. The concentrated CBH was subsequently used in fed batch process producing 89.2% ethanol yield. Furthermore, comparing just the cost of the raw materials sugarcane and CHB, the latter demonstrated to be a lower-cost feedstock for ethanol fermentation.
Keywords: Amylase; Rhizopus oligosporus; Solid state fermentation; Cassava bagasse hydrolysate; Glucose; Ethanol production